Research on Stateless Address Auto-Confi guration and Duplicate Address Detection in Space-Integrated-Ground Information Network - Yazheng CHEN; Hewu LI (天地一体化信息网络)
LEO (Low Earth Orbit) satellites with high mobility in space-integrated-ground information network cause ground user terminals change connected satellites continuously, so user terminals can't keep stable IPv6 addresses.SLAAC (Stateless Address Auto-Confi guration) in space-integrated-ground information network to provide stable IPv6 addresses was investigated, and an eff ective SLAAC and DAD (Duplicate Address Detection) mechanism was proposed.Aiming at the scenario where the ground equipment in the LEO satellite constellation constantly switches the LEO satellites, an IPv6 stateless address automatic confi guration and duplicate address detection mechanism was proposed.The scope of duplicate address detection was reduced by introducing ground position information and satellite orbit information, thereby eff ectively reduced signaling overhead for duplicate address detection.